Identifying and Prioritizing Suitable Financing Methods in Mosques of the Islamic Republic of Iran - Mahdi Karimi; Mohammad Hosin Gavam; Yaser Ahmadi Beni (تحقیقات مالی اسلامی (پیوسته))
Mosques not only have political, social and cultural roles, but also have an economic aspect. This research focuses on identifying and prioritizing suitable financial methods for mosques, exploring these priorities through library studies and expert interviews in the field. The study adopts an applied objective and an analytical-descriptive method based on documentation and expert opinions. Methods and criteria were identified based on the theme analysis method; Then, in the next step, the methods and criteria were prioritized with the help of paired comparison questionnaires and based on the Analytical Hierarchy (AHP) method, and finally the answers were combined and analyzed by the geometric mean method. The research findings indicate criteria such as increasing public participation, proper interaction with governance, enhancing budget efficiency, alignment with the status and dignity of mosques, and conformity with Imamia jurisprudence. Among these criteria, the highest importance, in order, is given to increasing public participation, alignment with the status and dignity of mosques, enhancing budget efficiency, proper interaction with governance, and conformity with Islamic jurisprudence. Based on this research, among the preferred financial methods for mosques in terms of tools, the most important are grassroots tools, technology-based financial tools, non-profit resource provisioning tools, for-profit resource provisioning tools, and investment-based tools, highlighting the effective role of the community in mosque financing. In terms of revenue-generating activities, mosque income-generating activities, charitable institutions, non-governmental public organizations, military entities, and governmental aids hold the highest importance in financing mosques.